THE WATER LEVEL CONTROL USING HEDGE ALGEBRAS - Hưng, Vũ Chấn; Tuấn, Hoàng Văn; Phu, Đặng Thành; Minh, Nguyễn Duy (Vietnam Journal of Science and Technology, 2012)
SUMMARY The paper aims to show an applicability of the algebraic to solving problems of fuzzy system Koster control. The results of the experimentation show that the new method based on hedge algebras is much simpler and easy to control a real process. Because in this approach, linguistic domains of linguistic variables can be considered as hedge algebras and in the case their elements can be ordered linearly by their own meaning, they are considered as linear hedges algebras. So that, an algebraic approach to term-domains of linguistic variables is quite different from the fuzzy sets one in the representation of the meaning of linguistic terms. In the algebraic approach, the meaning of a term is represented by the semantics based-relationships between this term and the remaining ones, while in the fuzzy sets approach the meaning of a term is expressed by only one fuzzy set alone, but not by relationships between fuzzy sets. It guarantees that the semantics-based order of a terms-domain is ‘similar’ to the order of the corresponding reference domain and, therefore, one can construct an appropriate SQM which preserves the essential relationships between the terms occurring in a fuzzy model.